Impact of inter-species hybridisation on antifungal drug response in the Saccharomyces genus - Federico Visinoni; William Royle; Rachel Scholey; Yue Hu; Soukaina Timouma; Leo Zeef; Edward J. Louis; Daniela Delneri (BMC Genomics)
Abstract Background Antifungal drug resistance presents one of the major concerns for global public health, and hybridization allows the development of high fitness organisms that can better survive in restrictive conditions or in presence of antifungal agents. Hence, understanding how allelic variation can influence antifungal susceptibility in hybrid organisms is important for the development of targeted treatments. Here, we exploited recent advances in multigenerational breeding of hemiascomycete hybrids to study the impact of hybridisation on antifungal resistance and identify quantitative trait loci responsible for the phenotype. Results The offspring of Saccharomyces cerevisiae x S. kudriavzevii hybrids were screened in the presence of six antifungal drugs and revealed a broad phenotypic diversity across the progeny. QTL analysis was carried out comparing alleles between pools of high and low fitness offspring, identifying hybrid-specific genetic regions involved in resistance to fluconazole, micafungin and flucytosine. We found both drug specific and pleiotropic regions, including 41 blocks containing genes not previously associated with resistance phenotypes. We identified linked genes that influence the same trait, namely a hybrid specific ‘super’ QTL, and validated, via reciprocal hemizygosity analysis, two causal genes, BCK2 and DNF1. The co-location of genes with similar phenotypic impact supports the notion of an adaption process that limits the segregation of advantageous alleles via recombination. Conclusions This study demonstrates the value of QTL studies to elucidate the hybrid-specific mechanisms of antifungal susceptibility. We also show that an inter-species hybrid model system in the Saccharomyces background, can help to decipher the trajectory of antifungal drug resistance in pathogenic hybrid lineages.